2022
DOI: 10.3390/ijerph192114515
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Catalytic Ozonation of Multitype VOCs over Zeolite-Supported Catalysts

Abstract: Volatile organic compounds (VOCs) are an important source of air pollution, harmful to human health and the environment, and important precursors of secondary organic aerosols, O3 and photochemical smog. This study focused on the low-temperature catalytic oxidation and degradation of benzene, dichloroethane, methanethiol, methanol and methylamine by ozone. Benzene was used as a model compound, and a molecular sieve was selected as a catalyst carrier to prepare a series of supported active metal catalysts by im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The signal intensity at 2.003 decreased as follows: 30WO 3 /20ZrO 2 –Hβ > 35WO 3 /20ZrO 2 –Hβ > 25WO 3 /20ZrO 2 –Hβ > 20WO 3 /20ZrO 2 –Hβ > 15WO 3 /20ZrO 2 –Hβ > 20ZrO 2 –Hβ. These results further indicted that 30WO 3 /20ZrO 2 –Hβ has the highest O-vacancy concentration …”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…The signal intensity at 2.003 decreased as follows: 30WO 3 /20ZrO 2 –Hβ > 35WO 3 /20ZrO 2 –Hβ > 25WO 3 /20ZrO 2 –Hβ > 20WO 3 /20ZrO 2 –Hβ > 15WO 3 /20ZrO 2 –Hβ > 20ZrO 2 –Hβ. These results further indicted that 30WO 3 /20ZrO 2 –Hβ has the highest O-vacancy concentration …”
Section: Resultsmentioning
confidence: 63%
“…These results further indicted that 30WO 3 /20ZrO 2 −Hβ has the highest O-vacancy concentration. 48 Figure 6 shows the Zr 3d, Si 2p, W 4f, and O 1s XPS spectra of xWO 3 /20ZrO 2 −Hβ, and Table 1 lists the surface atomic concentration of O according to XPS analysis. As shown in Figure 6a 26 As listed in Table 1, the ratio of W 5+ / (W 5+ +W 6+ ) (calculated based on the peak area of XPS spectra) was increased from 7.30% to 12.31% as the loading of WO 3 increased from 0 to 30 wt %.…”
Section: Catalyst Preparationmentioning
confidence: 99%
“…However, in the XRD curve of the Co2.5-Cr1.5 catalyst, the diffraction peak intensity of the Al 2 O 3 structure is weakened, and the diffraction peaks of Cr 2 O 3 and CoO x can hardly be seen, indicating that CoO x has good dispersion on the catalyst surface. After loading CoO x , the relative intensities of all peaks gradually decrease, indicating the enhancement of the metal interaction …”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the enhancement of catalytic ozonation involves the adsorption of ozone or pollutant or both of them on the catalyst surface, leading to the formation of free radicals, which react with non-adsorbed species in the bulk liquid. Therefore, the surface characteristics of the catalyst play an important role in the oxidation [32]. Solution pH is one of the most important factors affecting oxide surface properties.…”
Section: Effect Of Phmentioning
confidence: 99%